Economic and Mathematical Modeling of Enterprises’ Demand for Labor Power in the Era of Digital Economy - Dmitriyevich Sekerin, Vladimir; Nikolaevich Dudin, Mikhail; Veniaminovich Skubriy, Evgeniy; Evgenyevna Gorokhova, Anna; Vasilevich Komlatsky, Grigori (International Journal of Engineering and Technology, 2018)
The article presents an economic and mathematical model of enterprisesâ€™ demand for labor power in the form of a complex function of demand for the products of the enterprise in combination with the specific characteristics of the production process. In the presented economic and mathematical model, the demand for labor power is considered to be dependent on both the labor price and the prices of other production factors.Â Â